Focus on Education. Entrepreneurship, soft skills and the ancient world - Caggiano, Valeria; Costa, Cosimo (Studi sulla Formazione/Open Journal of Education, 2023)
The need for education aimed increasingly not only at technical skills, when at adopting a holistic approach with the goal of developing entrepreneurial competence. The focus on soft skills training as an attribute of an entrepreneurial worldview results in the search for training methodologies aimed at critical thinking. The use of an Example from the ancient world, the behavior of Marcus Aurelius who of duty and profession knew how to make the good of his empire.